2008
DOI: 10.1007/s00467-008-0777-2
|View full text |Cite
|
Sign up to set email alerts
|

Urine erythrocyte morphology in patients with microscopic haematuria caused by a glomerulopathy

Abstract: The evaluation of urinary erythrocyte morphology (UEM) has been proposed for patients with isolated microscopic haematuria (IMH) to early orientate the diagnosis towards a glomerular or a nonglomerular disease. However, to date, the role of this test in patients with IMH has very rarely been investigated. Sixteen patients (ten children, six adults) with persistent IMH classified as glomerular on the basis of repeated UEM evaluations (55 urine samples, two to eight per patient) were submitted to renal biopsy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…It has been reported that the frequency of MH can be as high as 1%, although different reports have mentioned frequencies as high as 20% of the general population [1]. It is unknown what portion of MH in the general population is of hereditary nature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the frequency of MH can be as high as 1%, although different reports have mentioned frequencies as high as 20% of the general population [1]. It is unknown what portion of MH in the general population is of hereditary nature.…”
Section: Introductionmentioning
confidence: 99%
“…Although dipstick testing is easy to perform in general practice, the morphology of urinary red blood cells (RBC) has been advocated as a fine diagnostic tool to differentiate between glomerular and nonglomerular causes of hematuria [6,7,8]. In glomerular hematuria, the variation in size and shape of the urinary RBC is increased, and such RBC are generally called dysmorphic RBC (dRBC).…”
Section: Introductionmentioning
confidence: 99%
“…Distinctive features of glomerular hematuria include red cell casts, protein excretion exceeding 500 mg/day at a time when there is no gross bleeding, a dysmorphic appearance of most (>80%) red cells (particularly if >5% acanthocytes), brown to cola-colored urine with gross hematuria and lower mean corpuscular volume (MCV) of RBC based on coulter analysis of urine. [35] Although helpful if present, the absence of these findings does not exclude glomerular disease. When persistent hematuria is essentially the only manifestation of glomerular disease, one of three disorders is most likely namely Ig-A nephropathy, Alport syndrome, and thin basement membrane nephropathy (gross hematuria unusual).…”
Section: Discussionmentioning
confidence: 99%